Neuropeptide Mapping of Dimmed Cells of Adult Drosophila Brain. - Diesner, M.; Predel, R.; Neupert, S. (Journal of the American Society for Mass Spectrometry, 2018)
Neuropeptides are structurally highly diverse messenger molecules that act as regulators of many physiological processes such as development, metabolism, reproduction or behavior in general. Differentiation of neuropeptidergic cells often corresponds with the presence of the transcription factor DIMMED. In the central nervous system of the fruit fly Drosophila melanogaster, DIMMED commonly occurs in neuroendocrine neurons that release peptides as neurohormones but also in interneurons with complex branching patterns. Fly strains with green fluorescence protein (GFP)-expressing dimmed cells make it possible to systematically analyze the processed neuropeptides in these cells. In this study, we mapped individual GFP-expressing neurons of adult D. melanogaster from the dimmed (c929)>GFP line. Using single cell mass spectrometry, we analyzed 10 types of dimmed neurons from the brain/gnathal ganglion. These cells included neuroendocrine cells with projection into the retrocerebral complex but also a number of large interneurons. Resulting mass spectra not only provided comprehensive data regarding mature products from 13 neuropeptide precursors but also evidence for the cellular co-localization of neuropeptides from different neuropeptide genes. The results can be implemented in a neuroanatomical map of the D. melanogaster brain. Graphical Abstract ?.